Mycolic Acids from “Noncultivable” Mycobacteria - Etemadi, A. H. (1974)
Chromatographic analysis, coupled to mass spectrometry with a high-resolution mass spectrometer, of materials isolated from skin lesions of patients with lepromatous leprosy allows the recognition of characteristic mycobacterial products, mycolic acids. This finding indicates that the “noncultivable” bacteria responsible for leprosy are mycobacteria.